2023
DOI: 10.1038/s41588-023-01518-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ancestry genome-wide study identifies effector genes and druggable pathways for coronary artery calcification

Maryam Kavousi,
Maxime M. Bos,
Hanna J. Barnes
et al.

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 108 publications
2
11
0
Order By: Relevance
“…Neither gene had previously been reported associated with CAC. 22,25,31 Furthermore, despite common variant associations near these genes with CAD, the suspected role of ARVCF and ATP1B1 in the development of atherosclerosis has not been well studied. ARVCF is a member of the catenin family, which plays an important role in cell adhesion and communication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither gene had previously been reported associated with CAC. 22,25,31 Furthermore, despite common variant associations near these genes with CAD, the suspected role of ARVCF and ATP1B1 in the development of atherosclerosis has not been well studied. ARVCF is a member of the catenin family, which plays an important role in cell adhesion and communication.…”
Section: Discussionmentioning
confidence: 99%
“…All CAD variants, except rs55730499 near LPA, have also previously been identified as associated with CAC in published CAC GWAS. 22,25,26 No SNVs met the Bonferroni-corrected threshold for significance in the interaction test, but 17 candidate variants were nominally significant (P int and P joint <0.05). Fifteen SNVs were in loci that had not previously been identified with CAC (Table 1).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The modest added predictive value shown by recent studies such as by [Elliott et al, 2020] could partly be due to the missing genetic components hidden within the genetic architecture of intermediate phenotypes of CVD, such as coronary artery calcification (CAC), that are involved in the pathogenesis of CVD. Indeed, although there is shared etiology between CVD and CAC, a recent comprehensive GWAS study of CAC found several new CAC associated genes that have so far not been reported to be associated with CVD [Kavousi et al, 2023]. CAC score, a measure of the amount of calcified plaque in coronary arteries, is a highly reliable indicator of cardiovascular disease beyond the established CVD risk variables [Detrano et al, 2008; Greenland et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the current study was to investigate whether GRS for CAC (CAC GRS) is associated with angiographically or morphometrically verified CAD in three European cohorts. The CAC GRS was calculated using genetic summary statistics from the most recent GWAS study of CAC [Kavousi et al, 2023]. We aimed to confirm the link between CAC associated SNPs and calcification by studying the association of CAC GRS with calcification areas measured in autopsy coronary arteries.…”
Section: Introductionmentioning
confidence: 99%